Sodium Channels and Local Anesthetics—Old Friends With New Perspectives - Körner, Jannis; Albani, Simone; Sudha Bhagavath Eswaran, Vishal; Roehl, Anna B.; Rossetti, Giulia; Lampert, Angelika (Frontiers in Pharmacology, 2022)
The long history of local anesthetics (LAs) starts out in the late 19th century when the content of coca plant leaves was discovered to alleviate pain. Soon after, cocaine was established and headed off to an infamous career as a substance causing addiction. Today, LAs and related substances – in modified form – are indispensable in our clinical everyday life for pain relief during and after minor and major surgery, and dental practices. In this review, we elucidate on the interaction of modern LAs with their main target, the voltage-gated sodium channel (Navs), in the light of the recently published channel structures. Knowledge of the 3D interaction sites of the drug with the protein will allow to mechanistically substantiate the comprehensive data available on LA gating modification. In the 1970s it was suggested that LAs can enter the channel pore from the lipid phase, which was quite prospective at that time. Today we know from cryo-electron microscopy structures and mutagenesis experiments, that indeed Navs have side fenestrations facing the membrane, which are likely the entrance for LAs to induce tonic block. In this review, we will focus on the effects of LA binding on fast inactivation and use-dependent inhibition in the light of the proposed new allosteric mechanism of fast inactivation. We will elaborate on subtype and species specificity and provide insights into modelling approaches that will help identify the exact molecular binding orientation, access pathways and pharmacokinetics. With this comprehensive overview, we will provide new perspectives in the use of the drug, both clinically and as a tool for basic ion channel research.